2007
DOI: 10.1111/j.1365-4632.2007.03393.x
|View full text |Cite
|
Sign up to set email alerts
|

Solitary and multifocal oral melanoacanthoma

Abstract: Multifocal oral melanoacanthoma appears to demonstrate some demographic and clinical variations from the solitary type of lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 22 publications
3
44
0
2
Order By: Relevance
“…(See also Refs. [6,7,8,9,10] and references therein.) Energy transferred to the plasma from the moving quark will cause the energy density of the plasma, in the vicinity of the quark, to deviate from its equilibrium value.…”
mentioning
confidence: 99%
“…(See also Refs. [6,7,8,9,10] and references therein.) Energy transferred to the plasma from the moving quark will cause the energy density of the plasma, in the vicinity of the quark, to deviate from its equilibrium value.…”
mentioning
confidence: 99%
“…In contrast, buccal mucosa is usually the most affected site in the solitary cases (4,6). Solitary or multifocal, they are thought to have a reactive nature and usually they regress spontaneously or after incomplete removal, such as an incisional biopsy (3,5,6). Clinically, OMA presents as a black or brownish lesion with a flattened surface (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…It may present as a solitary or multifocal lesion; however, these two variants exhibit different demographic features (5). According to Yaron et al, only about 53 patients with 72 cases of oral MA have been reported in the literature (43 solitary and 10 multifocal) (5). Although a female predominance has been observed in both variants, multifocal OMA presents an equal gender distribution and tends to occur more frequently on the palate (5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations